2021
DOI: 10.4239/wjd.v12.i3.278
|View full text |Cite
|
Sign up to set email alerts
|

Altered spontaneous brain activity in patients with diabetic optic neuropathy: A resting-state functional magnetic resonance imaging study using regional homogeneity

Abstract: BACKGROUND Diabetes is a common chronic disease. Given the increasing incidence of diabetes, more individuals are affected by diabetic optic neuropathy (DON), which results in decreased vision. Whether DON leads to abnormalities of other visual systems, including the eye, the visual cortex, and other brain regions, remains unknown. AIM To investigate the local characteristics of spontaneous brain activity using regional homogeneity (ReHo) in patients with DON. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Alterations of cortical signals can be used to locate cortical functional areas and further study brain functions [ 32 ]. Recently, a lot of rs-fMRI methods were used to observe the brain activities in DON patients, like degree centrality [ 33 ], functional connection density [ 34 ], regional homogeneity [ 35 ] and voxel mirrored homotopic connectivity [ 36 ] methods (details in Table 3 ). This study is the first to use the dALFF method which was ALFF combined with sliding window to reveal the temporal variability of regional intrinsic cerebrum activities in DON patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of cortical signals can be used to locate cortical functional areas and further study brain functions [ 32 ]. Recently, a lot of rs-fMRI methods were used to observe the brain activities in DON patients, like degree centrality [ 33 ], functional connection density [ 34 ], regional homogeneity [ 35 ] and voxel mirrored homotopic connectivity [ 36 ] methods (details in Table 3 ). This study is the first to use the dALFF method which was ALFF combined with sliding window to reveal the temporal variability of regional intrinsic cerebrum activities in DON patients.…”
Section: Discussionmentioning
confidence: 99%
“…MRI (RS-fMRI) research has become a hot spot. RS-fMRI is an imaging technique that explores changes in the function of the whole brain and its functional connections [ 7 ]. The imaging principle is as follows: when the activity of neurons in the local brain area increases, it causes an increase in local oxygen consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Regional homogeneity (ReHo) is a technique for analyzing rs-fMRI results that has been normally applied in clinical practice. Recent studies on the application of the ReHo method to analyze neuroimaging changes are shown in Table 1 (Tononi et al, 1998 ; Xiang et al, 2018 ; Liao et al, 2019 ; Shao et al, 2019 ; Wen et al, 2019 ; Li et al, 2020 ; Guo et al, 2021 ). By calculating the Kendall coefficient consistency of voxel dynamic fluctuation time-series in a specific cluster, the local synchronization of spontaneous rs-fMRI signals is explored, which represents essential data for normal brain activity ( Fang et al, 2021 ; Gaubert et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%